Developing thinking skills in the classroom: a systematic review - Bracho Mosquera, Aaron Samuel; Román-Mireles, Amarelys; Rodríguez-Álvarez, Aida Maygualida; Carbache Mora, César; Ormaza Esmeraldas, Elizabeth del Carmen; Vera Barrios, Bertha Silvana; Rodríguez Vásquez, Mario Pedro; Buelna-Sánchez, Rogelio; De La Paz Rosales, María Teresa De Jesús; Nieves-Lizárraga, Daniel Omar; Velarde-Osuna, Denisse Viridiana; Olguín-Martínez, Cynthia Michel; et al. (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
A person’s thinking skills are his or her mental abilities for the construction and organization of knowledge. The present study aimed to analyze the development of thinking skills in the classroom during the period 2019-2023. The study was based on a comprehensive literature assessment that followed PRISMA guidelines to extract 15 articles from major databases, including Scopus, Scielo, Latindex, and Web of Science. The results reveal a 33,3 % increase in research in 2021, with 66,7 % of those articles coming from Peru in the field of education. In conclusion, the increase in studies examining thinking skills is crucial in various areas of life, as it lays the foundation for individuals to act and think in a generalized way and develop broad perspectives, which are fundamental to overcome everyday life which are crucial for the development of reasoning skills.